Antioxidative recovery responses of Germinated Rough Rice (GRR) and Germinated Brown Rice (GBR) from various solvents and their potential towards reactive oxygen species quenching capacity - Ahmad, Zalinah; Thuraisingam, Shamini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Health promoting properties which generated worldwide interest in germinated rough rice (GRR) and germinated brown rice (GBR) are attributed largely by the bioactive compounds in the rice bran. Therefore, in the present study, antioxidant activities from gradient methanol and ethanol solvents followed by fractionations were evaluated. Methods: GRR and GBR crude extracts were successively obtained from two concentrations of metha- nol (80% and 100%) and ethanol (50% and 70%). They were further analyzed for 2,2-diphenyl-1-picrylhydrazyl (DPPH), Trolox Equivalent Antioxidant Capacity (TEAC) and Ferric Reducing Antioxidant Power (FRAP) assays. From the potent crude extract dissolved in water, they were sequentially subjected to fractionation using solvents with increasing polarity pattern, namely hexane fraction (HF), ethyl acetate fraction (EAF) and water fractions (WF ). Re- sults: WF belonging to both GRR and GBR generally possessed better antioxidant characteristics, demonstrated high TPC with GBR; 101.9 ± 0.2 mg GAE/g and GRR; 63.7 ± 1.2 mg GAE/g. GRR-WF exhibited high DPPH and TEAC with 63.68 mg TEA/g and 80.30 mg TEA/g respectively. GBR exhibited high DPPH in WF with 46.17 mg TEA/g but demonstrated high in ABTS in EAF fraction with 71.60 mg TEA/g. Both GRR and GBR showed high FRAP values in WF with 45.31 and 19.68 mg GAE/g respectively. Conclusion: Hence, it is proven that GBR and GRR owing to their antioxidant activities possess potential benefits which in turn has increased their competence as an emerging natural and valuable health food.